2012
DOI: 10.1007/s11164-012-0811-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of Yb-doped LiFePO4/C composites as cathode materials for lithium-ion batteries

Abstract: LiFePO 4 /C and LiYb 0.02 Fe 0.98 PO 4 /C composite cathode materials were synthesized by simple solution technique. The samples were characterized by X-ray diffraction, scanning electron microscope, and thermogravimetric-differential thermal analysis. Their electrochemical properties were investigated by cyclic voltammetry, four-point probe conductivity measurements, and galvanostatic charge and discharge tests. The carbon-coated and Yb 3? -doped LiFePO4 sample exhibited an enhanced electronic conductivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, the electronic conductivity of LiCoO 2 has been increased by over two orders of magnitude up to about 0.5 S/cm by partial substitution of Co 3+ by Mg 2+ and compensating hole creation by West et al [91]. Besides, Hüseyin Göktepe reported the improvement of electronic conductivity of LiFePO 4 by Yb 3+ -doping up to 1.9 × 10 −3 S/cm [90].…”
Section: Electronic Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the electronic conductivity of LiCoO 2 has been increased by over two orders of magnitude up to about 0.5 S/cm by partial substitution of Co 3+ by Mg 2+ and compensating hole creation by West et al [91]. Besides, Hüseyin Göktepe reported the improvement of electronic conductivity of LiFePO 4 by Yb 3+ -doping up to 1.9 × 10 −3 S/cm [90].…”
Section: Electronic Resistancementioning
confidence: 98%
“…Hence, the improvement of electronic conductivity is necessary to enhance the cell performance. As a result, many researchers have focused on improving electronic conductivity of electrode by surface coating or introducing conductive additives into the electrode materials [88,89] and improving the intrinsic electronic conductivity of active material by doping [90,91]. Carbon [88,[92][93][94], conducting polymer [95][96][97][98], and silver [99] etc.…”
Section: Electronic Resistancementioning
confidence: 99%
“…However, due to its rigid orthorhombic olivine structure, the intrinsic electronic conductivity of LFP and Li + diffusion rate is considerably low to reach full theoretical capacity during battery operation [1][2][3]. Different technical approaches have been used to overcome these drawbacks, such as: doping LFP with supervalent cations [3][4][5], reduction of particle size to nanoscale [3,6] and/or particle coating with carbon based materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…By titanium doping, Wu L. et al [1] observed LFP capacity increase from125 to 150 Ah/kg at 0.1C discharge rate. Göktepe H. et al [8] reported the electronic conductivity of 1.9×10 -3 S/cm and capacity of 146 Ah/kg obtained by combining Yb 3+ doped and carbon coated LFP to form LiYb 0.02 Fe 0.98 PO 4 /C composite. Similarly, through the variation of lanthanum amounts doped in LFP, Cho et al [9] found out that with 1% lanthanum content (LiFe 0.99 La 0.01 PO 4 /C), the LFP structure remained unchanged, meanwhile, its capacity increased from 104 to 156 Ah/kg at 0.2C discharge rate and exhibited good cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [29] thought Ni + -doping can decrease the particle size of LiFePO 4 . Hüseyin Göktepe [30] prepared LiFePO 4 /C Yb-doped with the specific capacity of 146 mAh g −1 at 0.1 C.…”
Section: Introductionmentioning
confidence: 99%